Matter, life, and generation : - Roe, Shirley A. (Cambridge University Press, 2001)
In the eighteenth century, two rival theories of organic generation existed. This book takes the debate beyond its observational basis and shows that at issue were not only specific embryological problems but also fundamental philosophical questions about the natural world and the way science should explain it.